Designing a Crowdfunding Process Model in Knowledge-Based Companies with a Theme Analysis Approach - Saba Amiri (پژوهش‌های مدیریت عمومی, 2022)
AbstractThis study with the aim of designing a crowdfunding process model in knowledge-based companies was done. The research method was qualitative from theme analysis. The key experts studied were managers and employees of knowledge-based companies in three provinces of Hamadan, Kurdistan and Kermanshah, along with managers with expertise from public and private institutions. The criteria for selecting experts was having at least 5 years of work experience or research experience in relation to the research topic and the criteria of agreement, key role and participation. Experts were selected using judgmental and snowball sampling methods and data collection continued until theoretical saturation was achieved (40 people). Data collection tools were semi-structured interviews.Clark and Braun six-step method was used for data analyzing. In summary, the results showed that the crowdfunding process model in knowledge-based companies consists of 623 codes, 66 basic themes, 21 sub-organizing themes and 5 main organizing themes. Accordingly, the environmental and internal drivers of the knowledge-based company, along with appropriate strategic actions, expected consequences at the macro level and expected consequences at the enterprise level, form the elements of the research process model.In a way, the drivers of the phenomenon of "crowdfunding" are formed, and consequently, strategic actions shape the consequences.IntroductionFinancing for the development of entrepreneurial ideas has always been a major obstacle for entrepreneurs and business owners, and raising capital, especially from external sources, is difficult for all entrepreneurs. In this regard, crowdfunding is one of the newest methods of financing entrepreneurial projects to develop and commercialize the ideas of entrepreneurs. Most entrepreneurs face difficulties in raising capital in the early stages of their business because they cannot convince potential investors of their ideas. On the other hand, knowledge-based companies, as a driver of economic growth and development of the country, generally ask banks and financial institutions to provide the capital they need, while despite the governing structure of banks and central bank rules, the necessary flexibility to provide. Therefore, financing of knowledge-based companies in such a way that the appropriate capital is provided to these companies at the right time and in sufficient and correct manner, is of great importance, especially which 139 knowledge-based companies are operating in Kermanshah, Kurdistan and Hamedan provinces. Studies also show that there is a serious theoretical gap in the literature in this field. Therefore, the present study was conducted with the aim of designing and explaining the crowdfunding process model for knowledge-based companies.Case studyThe case study was knowledge-based companies in Kermanshah, Kurdistan and Hamedan provinces.Theoretical frameworkCrowdfunding is a way to raise funds from a large audience rather than investors. In crowdfunding, individuals provide financial assistance to the company. Because knowledge-based companies, face many challenges due to innovation, short technology life cycle, need for new markets, complex non-linear business process, and uncertain future, traditional financial institutions such as banks do not have the necessary expertise to Challenges for the advancement of these companies, despite the high savings and turnover if successful, are reluctant to provide facilities or investment in these companies.Given the emergence of the co-financing method, the theoretical gap in this area is very serious and very little research has been found to address this issue.Materials and MethodsThe present research is applied from the point of view of purpose and in terms of method, it is a qualitative type of theme analysis. Clarke & Braun (2006) method was used for data analyzing. The key experts studied were managers and employees of knowledge-based companies in three provinces of Hamadan, Kurdistan and Kermanshah, along with managers with expertise from public and private institutions. In this study, judgmental and snowball purposeful sampling methods were used, based on which, 40 people were interviewed semi-structured and sampling adequacy was achieved to achieve theoretical data saturation. In order to verify and validate the results of the theme analysis, qualitative validation criteria including acceptability and reliability were examined. Validity of interviews by triangulation method; examining the previous researches and asking questions in several ways, and their reliability was confirmed by the recoding method and calculating the coding agreement and calculating the Holstien reliability coefficient of 0.79.Discussion and ResultsDuring this process, 623 codes were extracted. Then, by examining the initial codes given to each of the concepts and removing the similar, incomplete and irrelevant concepts that existed in the initial coding, 66 basic concepts or themes were counted. In the review, during several stages of reviewing and refining the selected codes, 21 sub-organizing themes were formed. In the fifth stage, the researchers, by performing reciprocal actions among the sub-organizing themes extracted from the previous stage, sought to categorize them into higher-level categories. In this regard, the sub-organizer themes were divided into 5 general categories based on content and appearance. The final stage of the theme analysis included the presentation of the final report. Accordingly, the environmental and internal drivers of the knowledge-based company are the basis and cause of "crowdfunding" in the knowledge-based company, which also overlap with each other, because some basic themes may have commonalities in these two main themes. And be influenced by each other. After that, crowdfunding, as the core of content analysis, leads to the formulation and design of a set of strategic actions in the form of a number of activities and processes. Finally, strategic actions have consequences at the macro level, which lead to the formation of consequences at the level of the knowledge-based company. Importantly, the set of expected outcomes at the enterprise level in a cycle goes back to the central phenomenon of this process model, which is the "crowdfunding in the knowledge-based company", and leads to its development.ConclusionThe research process model shows that environmental drivers, including socio-cultural conditions, economic conditions, political-legal conditions, infrastructural-technological conditions, market-related conditions, the role of public institutions, the role of the private sector and investors, and the financial collecting platform are all be relevant to the business environment of a knowledge-based company, be provided, can lead to the formation and development of "crowdfunding", because knowledge-based companies operate in an interactive and environmentally influenced ecosystem. In addition to these drivers, the driving factors associated with knowledge-based companies, including their organizational structure and the justifi ability of the venture capital scheme, are also important because they play a role in the development or non-development of "crowdfunding". According to the proposed process model, from the influence of the drivers, the central phenomenon of "crowdfunding" is formed, for the development of which strategic measures are designed in the model; Including the development of accurate feasibility study for the investable plan, re-engineering of the organizational structure of the knowledge-based company, the development of a value creation system for key stakeholders, the design of a precise and transparent financial mechanism and the development of a system for protecting intellectual property. Following this process pattern, the expected consequnses are formed at the macro and enterprise level. Therefore, to the extent that the environmental and internal factors of the knowledge-based company play a more promotional role and strategic measures are implemented correctly and accurately, the possibility of developing "crowdfunding" will increase.